2012
DOI: 10.1051/0004-6361/201118389
|View full text |Cite
|
Sign up to set email alerts
|

Interacting planetary nebulae

Abstract: We discuss the classification and orientation of planetary nebulae that interact with the interstellar medium throughout the Milky Way. A sample of 117 confirmed interacting planetary nebulae is used for this purpose. Our results indicate that the majority of interacting objects are located close to the Galactic plane, and ∼77% of them are located inside the Galactic thin disk. One third of the sample is less than 100 parsec from the Galactic plane and thus may interact with molecular and cold neutral clouds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 84 publications
1
29
0
Order By: Relevance
“…This PN-ISM interaction usually affects the nebular morphology, especially the outer structures. Observational studies (e.g., Borkowski et al 1990;Ramos-Larios & Phillips 2009;Sahai & Chronopoulos 2010;Ali et al 2012Ali et al , 2013Zhang et al 2012b;Sahai & MackCrane 2014;Ramos-Larios et al 2018) and theoretical modeling (e.g., Dgani & Soker 1998;Villaver et al 2003;Villaver 2004;Wareing et al 2007aWareing et al , 2007b NGC 6772 is the best candidate in our sample that shows possible interaction with the ISM. An extended, asymmetric halo is seen in H 2 emission (Figure 12, left).…”
Section: Possible Interaction With the Ismmentioning
confidence: 85%
See 1 more Smart Citation
“…This PN-ISM interaction usually affects the nebular morphology, especially the outer structures. Observational studies (e.g., Borkowski et al 1990;Ramos-Larios & Phillips 2009;Sahai & Chronopoulos 2010;Ali et al 2012Ali et al , 2013Zhang et al 2012b;Sahai & MackCrane 2014;Ramos-Larios et al 2018) and theoretical modeling (e.g., Dgani & Soker 1998;Villaver et al 2003;Villaver 2004;Wareing et al 2007aWareing et al , 2007b NGC 6772 is the best candidate in our sample that shows possible interaction with the ISM. An extended, asymmetric halo is seen in H 2 emission (Figure 12, left).…”
Section: Possible Interaction With the Ismmentioning
confidence: 85%
“…It is noteworthy that NGC 6772, NGC 6781, and NGC 6894 have already been identified as interacting PNe in Ali et al (2012).…”
Section: Possible Interaction With the Ismmentioning
confidence: 99%
“…Thanks to modern observational tools, the number of detected interacting planetary nebulae (IPNe) has increased during the last 20 years. Recently, Ali et al (2012; hereafter Paper I) presented a list of 117 objects confirmed as interacting planetary nebulae. In Paper I, we discussed the morphological classification and the Galactic orientation of the interaction regions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, their WZO1 phase regroups all the objects in their early phase of interaction where the only affected component (in the form of a bow-shock) is the surrounding faint halo of the otherwise still morphologically intact PN. The number of PNe in the WZO1 stage represents ∼26% of the whole sample of 117 objects compiled by Ali et al (2012), based mainly on observations coming from Ramos-Larios & Phillips (2009) and Corradi et al (2003). A cross check with the Hong Kong/AAO/Strasbourg Hα PN database (HASH) With the purpose to investigating the real shape of this diffuse halo, their kinematics, composition and ISM interaction in NGC 650-1, we have used Spitzer MIPS and WISE infrared images, new deep and high-resolution broad-and narrow-band optical images, and long-slit low-and high-dispersion spectroscopic observations.…”
Section: Introductionmentioning
confidence: 99%